Cover Image. (17th May 2021) - Ebner, Brendan C.; Donaldson, James A.; Murphy, Helen; Thuesen, Paul; Ford, Andrew; Schaffer, Jason; Keith, Philippe
Abstract : The cover image is based on the Original Article Waterfalls mediate the longitudinal distribution of diadromous predatory fishes structuring communities in tropical, short, steep coastal streams, by Brendan Ebner et al., https://doi.org/10.1111/fwb.13712 .